Glucagon-like peptide-1 receptor modulates cerebrospinal fluid secretion and intracranial pressure in rats - Mette N. Jensen; Ida M. E. Israelsen; Jonathan H. Wardman; Dennis B. Jensen; Daniel B. Andersen; Trine L. Toft-Bertelsen; Martin F. Rath; Jens Juul Holst; Mette M. Rosenkilde; Nanna MacAulay (Fluids and Barriers of the CNS)
Abstract Background Cerebrospinal fluid (CSF) is produced and absorbed at a balanced rate to maintain a constant intracranial pressure (ICP). The CSF dynamics are, however, disturbed in several pathological conditions, leading to elevated ICP, which may have fatal outcomes if left untreated. Treatment options for these conditions are limited to invasive neurosurgery, and novel pharmacological approaches to manage ICP in pathology are sought. Here, we aimed to demonstrate the potential of the glucagon-like peptide-1 receptor (GLP-1R) as such a target. Methods We administered male rats with intraperitoneal (i.p.) or intracerebroventricular (i.c.v.) GLP-1R agonist (exendin-4) or antagonist (exendin-9-39) followed by in vivo determination of CSF dynamics. GLP-1R expression in the CSF-secreting choroid plexus was demonstrated with RNAScope in situ hybridization and western blotting and transporter activity with radio-isotope flux assays. Results GLP-1R activation increased the CSF secretion rate with an associated elevation of the ICP, whereas inhibition of the receptor reduced the rate of CSF secretion. These effects were observed with central, but not peripheral, administration of the agonist and antagonist, suggesting receptor expression on the luminal, CSF-facing side of the choroid plexus, which aligned with GLP-1R-mediated modulation of luminally-expressed transporters in excised choroid plexus. Low level GLP-1R expression was demonstrated in the choroid plexus at mRNA and protein levels. Conclusion Modulation of GLP-1R affects CSF production, which suggests that GLP-1R-mediated signalling may have the potential to control ICP in pathological conditions with disturbed CSF homeostasis.